Визначення триптофану в молоці - Квітковська, Надія Петрівна; Іщенко, Віра Миколаївна; Кочубей-Литвиненко, Оксана Валер'янівна; Іщенко, Микола Володимирович (My University, 2023)
Tryptophan or L-tryptophan is one of the essential amino acids for the human body. An important component of the human diet, L-tryptophan is not only involved in protein synthesis in the body, but is also crucial for a number of metabolic functions. One of the important sources of tryptophan for the human body are dairy products, and their feature is the fact that milk itself contains the best ratio of tryptophan/competing amino acids, which is necessary for the synthesis of serotonin. Since tryptophan is thermolabile, one of the factors that can affect its content is heat treatment of milk. The standard and certified method for determining tryptophan in milk is high-performance liquid chromatography with fluorescence detection. Tryptophan belongs to fluorophores and fluoresces most strongly among all amino acids. It absorbs electromagnetic radiation with a wavelength of 290 nm and emits in the range of 300–350 nm. In the presented study, tryptophan was determined by the method of fluorescence spectroscopy without chromatographic separation of 18 samples of drinking milk from well-known Ukrainian producers of dairy products, which differed in the method of heat treatment and manufacturing technology. Fluorescence spectra were recorded on a Perkin-Elmer LS-55 fluorescence spectrometer; the content of dry skimmed milk residue and lactose in milk samples was determined on an ultrasonic milk analyzer “Ekomilk-Bond” (Bulgaria). Sample preparation of milk samples for the determination of tryptophan was carried out according to DSTU ISO 13904:2008. Research has shown that the content of tryptophan in milk samples from Ukrainian dairy producers ranges from 189.5 to 515.1 mg/l, which is basically consistent with literature data. Dependence of the method of heat treatment of milk on tryptophan content was not found. Obviously, first of all, the tryptophan content in milk will be influenced by the total protein content in the product.
Keywords: кафедра харчової хімії; кафедра технології молока і молочних продуктів; молочна продукція; флуоресценція; молекулярно-абсорбційна спектроскопія; dairy products; fluorescence; molecular absorption spectroscopy